Nghiên cứu sử dụng cây cỏ lác (Cyperus procerus) làm vật liệu hấp phụ Pb(II) trong nước. - Minh, Trần Lệ; Hải, Huỳnh Trung; Tanaka, Mikiya (Vietnam Journal of Chemistry, 2012)
This study is on sorption of lead ions on a new natural and abundant material, tall cyperus (Cyperus procerus Rottb.). The batch type experiments showed, tall cyperus was found to be useful sorbent for the removal of Pb(II) from aqueous solution. The effect of the contact time, pH, initial metal concentration, solid - liquid ratio... on the removal process were investigated. The maximum removal efficiency was 99.6% for Pb(II) at equilibrium pH 4.7. Equilibrium isotherms have been measured and modeled. The data were fitted well for the Langmuir adsorption isotherm as well as Freundlich adsorption model. Langmuir monolayer adsorption capacity was found to be 44.9 mg g-1 at 25oC. Further, the column data showed that tall cyperus can be reused at least several times for removing Pb(II) through the saturation – elution cycle. Tall cyperus is said to be a promising, inexpensive, and effective sorbent for lead ions from aqueous solution.